Strategic Planning of Information Systems Beauty Clinics with Ward and Peppard Model Approaches (Case Study: Virgina Aesthetics Company (Farina Beauty Clinic) - Pranata, Andi (Politeknik Negeri Madiun, 2020)
Virgina Aesthetic Company (Farina Beauty Clinic) is an organization or company engaged in the field of face and body skin care services. To be able to get a competitive advantage and be able to survive in tight competition, the strategy that can be done by a beauty clinic is differentiation and cost reduction. One of the things that can be done for cost-reduction is to make the business processes in the Beauty Clinic more efficient, one of the things that can be used for efficiency is Information Systems (IS) / Information Technology (IT). This research is an effort to build an information system strategic planning and application portfolio in the Virgina Aesthetic Company (Farina Beauty Clinic) that can provide optimal, well integrated and innovative contributions that can unite all supporting aspects in achieving clinical business strategies to increase its competitive value especially in health services.In preparing the information system strategic planning framework using the Ward and Peppard Model approach and in evaluating the elaboration of information systems strategic planning and business strategies using IT Balance Scorecard. Several analytical methods such as Value Chain Analysis, SWOT Analysis, PEST Analysis and Five Force Model Analysis are used to analyze internal and external business environments. Strategic Grid McFarlan Analysis is used to map the application portfolio. In the end this research resulted in a recommendation for the organization in the form of development priorities which were divided into two related matters, the establishment of an IS / IT unit and the development of an application portfolio that would support the sustainability of Virgina Aesthetics Company (Farina Beauty Clinic) Karawang.Â Â